Pengembangan Modul Interaktif Pencegahan Bullying Siswa Remaja dengan Model RnD - Hajar Mukarromah; Itsna Iftayani; Patria Jati Kusuma (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to develop a bullying prevention intervention module for adolescent students in junior high schools equipped with a game called "Si CeBul" which functions to provide an understanding of bullying, a chat card called "Titik Temu" which functions to guide interactive communication sessions, and a "stop bullying" puzzle. The approach of this study is Borg & Gall's research and development which is limited to five main stages, namely (1) Identification of Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, and (5) Design Revision. The study was conducted in Purworejo involving students who had been victims, perpetrators, witnesses of bullying. Data analysis techniques, researchers used qualitative and quantitative descriptive whose results became the basis for developing the resulting product. The level of feasibility of the bullying prevention intervention module was assessed through validation of materials and media by experts. The overall average of material validation was 80.83% classified as "Good", with the statement that it was appropriate and did not need to be revised, media validation 79.39 ... "Good", with the statement that the module was appropriate and did not need to be revised. However, there were input and suggestions from validators that required revision. The conclusion of the media and material validation is that this intervention module is suitable for use as an intervention module for adolescent bullying for teachers and guidance and counseling facilitators. The contribution of this research is the development of  bullying intervention module for teachers and guidance and counseling facilitators.